ANALISIS STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN JUMLAH MAHASISWA PADA LEMBAGA PENDIDIKAN CYZ - Ni Putu Mayun Swanitha; Sephy Lavianto; I Made Artana (Jurnal Informatika Teknologi dan Sains, 2022)
Abstract: CYZ educational institutions have used technology as a promotional medium to find new students. CYZ is an educational institution that has used technological developments to develop its business. CYZ uses social media and websites as one of the supporters in introducing campuses and finding new students. In this study, qualitative descriptive research was used. This method focuses on answering research questions related to Digital Marketing Strategy Analysis in Increasing the Number of Students at CYZ Educational Institutions, especially in the use of social media and websites. This study also uses SWOT analysis to analyze internal strengths and weaknesses, opportunities and threats externally, and to determine the position of CYZ's company. With the SWOT weighting being in quadrant I implementing an aggressive strategy, means that CYZ is in a ready condition to continue to grow and develop by utilizing strengths and seizing opportunities to the fullest.